2017
DOI: 10.1186/s13059-017-1378-9
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Arabidopsis thaliana to the Yangtze River basin

Abstract: BackgroundOrganisms need to adapt to keep pace with a changing environment. Examining recent range expansion aids our understanding of how organisms evolve to overcome environmental constraints. However, how organisms adapt to climate changes is a crucial biological question that is still largely unanswered. The plant Arabidopsis thaliana is an excellent system to study this fundamental question. Its origin is in the Iberian Peninsula and North Africa, but it has spread to the Far East, including the most sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
117
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(120 citation statements)
references
References 74 publications
1
117
2
Order By: Relevance
“…Particularly surprising was the finding that all African populations, including South Africans and Tanzanians, are native and that all sampled African individuals represent relicts when compared to the major Eurasian clade (Durvasula et al ., ). Other notable findings are that the island of Madeira harbors the most extremely diverged individuals sampled to date (Fulgione et al ., ) and that diverged samples from Central Asia (Tibet, Zeng et al ., ; Yunnan, Zou et al ., ; Western Himalayas, Tyagi et al ., ; the Altai Mountains, Yin et al ., ) suggest additional refugia.…”
Section: New Genomic Data From Outside Eurasia Challenge Our View Ofmentioning
confidence: 98%
See 3 more Smart Citations
“…Particularly surprising was the finding that all African populations, including South Africans and Tanzanians, are native and that all sampled African individuals represent relicts when compared to the major Eurasian clade (Durvasula et al ., ). Other notable findings are that the island of Madeira harbors the most extremely diverged individuals sampled to date (Fulgione et al ., ) and that diverged samples from Central Asia (Tibet, Zeng et al ., ; Yunnan, Zou et al ., ; Western Himalayas, Tyagi et al ., ; the Altai Mountains, Yin et al ., ) suggest additional refugia.…”
Section: New Genomic Data From Outside Eurasia Challenge Our View Ofmentioning
confidence: 98%
“…These two factors limited the scope of the conclusions that could be drawn. However, several recent studies examined complete genome sequences of accessions from outside Eurasia, including Africa (Durvasula et al ., ), Madeira (Fulgione et al ., ) and Central Asia (Zeng et al ., ; Zou et al ., ) and compared them to results from across Eurasia (1001 Genomes Consortium, ). These studies reveal several surprises and helped to reconcile previous inconsistencies, as outlined below.…”
Section: New Genomic Data From Outside Eurasia Challenge Our View Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Zou et al . () have studied A. thaliana accessions from China and shown that the population in the Yangtze River Basin arrived relatively recently. They also showed that genes associated with the immune response as well as flowering time were significantly enriched in the list of selected genes in the Yangtze population.…”
Section: Introductionmentioning
confidence: 99%